2009
DOI: 10.2965/jwet.2009.277
|View full text |Cite
|
Sign up to set email alerts
|

Children's Health Deficits due to Diarrhoea: Effects of Water Supply and Sanitation Systems in Slums with Different Water Logging Conditions

Abstract: This population-based epidemiologic study investigated the associations of individuals' sociodemographic statuses, sanitary systems and habits, water supply and drainage conditions with diarrhoea incidences among 707 children younger than 5 years who were living in slum communities with various water logging patterns in Dhaka, Bangladesh. We conducted a homevisiting survey during the pre-monsoon period from December 2006 to April 2007. Nine slum communities were selected that had been experiencing five differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…First, we found that there were predisposing causes for contracting diarrhoea in the non-flooded areas because the morbidity was present in the pre-and post-monsoon season, even though flooding did not occur at that time. As Mollah et al (2009) mentioned in their paper, this risk might be due to food, drinking water or hand-washing customs, which were not related to the flooding. Second, we found that flooding has an influence on diarrhoeal incidence because morbidity increased in the mid-monsoon season when flooding occurred, and this increase was observed in almost all com- munities (9 out of 10).…”
Section: Flood Analysismentioning
confidence: 88%
See 4 more Smart Citations
“…First, we found that there were predisposing causes for contracting diarrhoea in the non-flooded areas because the morbidity was present in the pre-and post-monsoon season, even though flooding did not occur at that time. As Mollah et al (2009) mentioned in their paper, this risk might be due to food, drinking water or hand-washing customs, which were not related to the flooding. Second, we found that flooding has an influence on diarrhoeal incidence because morbidity increased in the mid-monsoon season when flooding occurred, and this increase was observed in almost all com- munities (9 out of 10).…”
Section: Flood Analysismentioning
confidence: 88%
“…Data related to epidemiology were obtained through home visit surveys by Mollah et al (2009). They conducted a biweekly survey in April (pre-monsoon), September (mid-monsoon) 2007 and January (post-monsoon) 2008 via questionnaires and interviews of mothers of children under five years of age.…”
Section: Epidemiological Datamentioning
confidence: 99%
See 3 more Smart Citations